Gendering Madness and Doubling Disability in Jane Eyre - Sinha, Sunanda (The Grove - Working Papers on English Studies, 2021)
Jane Eyre has a well-designed structure of a bildungsroman that focuses on the pursuit of Jane’s desire and ignores the same for Bertha. The conceptual structure conveys a linear discourse to determine a prefixed understanding of Bertha, Jane, and Rochester. In Bertha’s context, the bildungsroman operates to deliver issues of race, gender, and disability in an existential quest to ascertain and establish her madness. There is a well-designed structural correspondence of bildungsroman, interplay of dark and light binary, the desire of Jane against the asexual Bertha, and the metaphor of fire in mapping the doubling. The literary devices serve as a dominant metaphorical barrier to normalcy in Thornfield. The paper considers this authorial viewpoint on Bertha’s sickness as a construct of a parallel gendered and a more potent conceptualisation of madness. In problematising madness, the paper argues a cultural narrative of representation that is affected by the impaired mind of Bertha. It will interrogate how the narrative systematically forges a doubling within which she is objectified, influenced, muted, bounded and characteristically disabled.